Democrazia cognitiva ed inclusione: l'educazione come principio di emancipazione secondo la prospettiva di Edgar Morin - Rossella Certini (Firenze University Press, 2022)
Today the future has been defined and thought out in a strictly economic and technological perspective. The "human dimension of man" finds more and more limited spaces within which to develop and progress, due to the pervasiveness of the media and the technique that guides, controls and nourishes them. Consumerism, ethnic hypertrophy, the emotional crisis that is affecting humanity globally are elements that risk eliminating diversity and raise individualism to power, thus denying the possibility for many to have access to common knowledge. In this weak and complicated situation, but with equally evident possibilities for change and improvement, the principle of cognitive democracy, a principle supported and repeatedly re-launched by Edgar Morin in his papers, fails and risks being weakened by the new false myths, for exemple the PIL. Morin has always indicated education as the main way to create inclusion, the way to build shared spaces, not to create separation, to rethink and redefine the complementarity of all knowledge. This has the objective of creating a free thinking community oriented towards the democratic principles of coexistence. Cognitive democracy, inclusion and education: an important trinomial that characterizes Morin's critical reflection on the possibilities of growth and development of a new phase in human life. New knowledge does not represent a danger or a limit for people, but an opportunity for growth for everyone.